2017
DOI: 10.4143/crt.2016.073
|View full text |Cite
|
Sign up to set email alerts
|

The Association between End-of-Life Care and the Time Interval between Provision of a Do-Not-Resuscitate Consent and Death in Cancer Patients in Korea

Abstract: PurposeWe explored the relationship between the use of each medical intervention and the length of time between do-not-resuscitate (DNR) consent and death in Korea.Materials and MethodsA total of 295 terminal cancer patients participated in this retrospective study. Invasive interventions (e.g., cardiopulmonary resuscitation, intubation, and hemodialysis), less invasive interventions (e.g., transfusion, antibiotic use, inotropic use, and laboratory tests), and the time interval between the DNR order and death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 16 publications
2
39
6
1
Order By: Relevance
“…and 68.1% in the two groups, which was higher than another study [17]. It suggested high prevalence of dysphagia at the EOL in older adults.…”
Section: Symptom Assessment and Management Skills Are The Key Contentcontrasting
confidence: 59%
See 1 more Smart Citation
“…and 68.1% in the two groups, which was higher than another study [17]. It suggested high prevalence of dysphagia at the EOL in older adults.…”
Section: Symptom Assessment and Management Skills Are The Key Contentcontrasting
confidence: 59%
“…Prognostication involves 3 key components: formulation of the patient's prognosis; communication of the patient's prognosis; and the patient or surrogate's interpretation of the communicated prognosis [18]. A study [17] had shown that early DNR consent can reduce the CPR attempt and other invasive treatments in patients with advanced cancer. The patients are more willing to accept a DNR decision when it was referred to as 'allowing natural death', when there is comprehensive information and when there are worse outcomes [19].…”
Section: Symptom Assessment and Management Skills Are The Key Contentmentioning
confidence: 99%
“…In Korea, DNR documentation is usually obtained only when death is very imminent. In previous studies of DNR documentation by Korean cancer patients [ 27 , 28 ], the median time interval from DNR consent to death ranges from 1.76 to 6 days, which was shorter than that reported in the United States [ 29 ]. This short time does not permit enough opportunity to elicit personal value and goals, to contemplate options, and to clarify preferences for treatment.…”
Section: Discussionmentioning
confidence: 85%
“…Decisions for LST in Korea are mostly discussed within a few days or weeks before death (4)(5)(6). Family members usually write a do-not-resuscitate document as surrogate decision makers for family members near death (5)(6)(7)(8). Furthermore, patients in the terminal stage are more likely to receive aggressive treatment with little curative effect (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%